2000
DOI: 10.1042/cs20000023
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin levels in serum and liver tissue in patients with chronic viral hepatitis and hepatocellular carcinoma

Abstract: Thrombocytopenia in liver diseases is considered to be due to splenic platelet pooling and accelerated destruction. Since thrombopoietin (TPO), a regulator of thrombopoiesis, is produced mainly in the liver, decreased production of TPO may account for thrombocytopenia in liver diseases. To address this issue, we measured serum TPO, using a sensitive sandwich ELISA, in 108 patients with chronic viral hepatitis, which included chronic hepatitis (CH) and liver cirrhosis (LC), and hepatocellular carcinoma (HCC), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…Further evidence that, in virally infected patients, the thrombocytopenia was, at least in part, extracorpuscularily immune-mediated, comes from our observation of splenomegaly and platelet count in groups B and C (hepatitis B and C infections) (not statistically significant), whereas, in contrast, the significance between splenomegaly and thrombocytopenia in nonviral diseases (PBC and alcohol-induced) suggests a direct platelet-retaining effect of the enlarged spleens. In contrast to a recent Japanese study (Okubo et al, 2000) that found a significant correlation between platelet count and splenomegaly, we only can confirm this relationship in non-viral liver disease (groups A and D); the serum TPO levels in the Japanese study were also reduced in less severe liver disease stages. These findings might be relevant in substitutive treatment of thrombocytopenic liver diseased patients with TPO.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Further evidence that, in virally infected patients, the thrombocytopenia was, at least in part, extracorpuscularily immune-mediated, comes from our observation of splenomegaly and platelet count in groups B and C (hepatitis B and C infections) (not statistically significant), whereas, in contrast, the significance between splenomegaly and thrombocytopenia in nonviral diseases (PBC and alcohol-induced) suggests a direct platelet-retaining effect of the enlarged spleens. In contrast to a recent Japanese study (Okubo et al, 2000) that found a significant correlation between platelet count and splenomegaly, we only can confirm this relationship in non-viral liver disease (groups A and D); the serum TPO levels in the Japanese study were also reduced in less severe liver disease stages. These findings might be relevant in substitutive treatment of thrombocytopenic liver diseased patients with TPO.…”
Section: Discussioncontrasting
confidence: 55%
“…However, clinical standard committees are reluctant to favour either serum or plasma for quantitation of TPO. Experiments that spike either material with TPO, in the quest for the ideal sample type for enzymelinked immunosorbent assay (ELISA), are still rare, with serum being used more frequently nowadays for quantitative TPO estimation, (Shimodaira et al, 1996;Okubo et al, 2000;Peck-Radosavljevic et al, 2000). However, the consistent peak values in the four patient groups as well as the low interassay variability suggest that serum is as good an analyte as plasma.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in hepatic TPO production has been proposed as an important concomitant cause of the reduction in platelet production in patients with chronic liver disease. Some studies have shown that TPO production correlates with disease stage and liver function in patients with chronic liver disease [21,22]. In this study, it can be presumed that most patients did not experience a decrease in TPO, because almost all patients with HBV and/or HCV infection had normal baseline liver function.…”
Section: Discussionmentioning
confidence: 80%
“…This result was similar to Stockelberg et al, Goulis et al with correlation that reported no correlation between serum TPO level and platelet counts in liver cirrhosis. 9,14,16 This result correlation between serum TPO level and platelet counts in liver cirrhosis patients, showed by a low serum TPO level in thrombocytopenia patients rather than normal platelet patients. In contrast, Tamel et al reported that serum TPO was correlate negatively with platelet counts in liver cirrhosis patients (r = -0.71; p < 0.001).…”
mentioning
confidence: 85%
“…Serum TPO level also correlate to clinical lower serum TPO the more severe its liver cirrhosis. [8][9][10][11][12] Otherwise, several studies (Temel et al, Stockelberg et al, and Yilmaz et al) showed that serum TPO in liver cirrhosis and liver fibrosis patients was not found to be lower than healthy individual and did [8][9][10][11][12][13][14][15][16] Serum TPO were mainly regulated by total mass of platelet and circulating megakaryocyte by receptor mediated clearance mechanism. [17][18][19] TPO was a main regulator of platelet production, so that serum TPO become a recommended laboratory test to evaluate liver cirrhosis patients with thrombocytopenia.…”
mentioning
confidence: 99%